Demonstration of biological activity and nucleotide sequence of an in vitro synthesized clone of the Moloney murine sarcoma virus mos gene. - Donoghue, D J (1982)
A clone of the Moloney murine sarcoma virus mos gene derived by in vitro reverse transcription was characterized. When assayed for focus formation by DNA transfection on NIH/3T3 cells, this clone was biologically inactive, presumably due to the absence of a long terminal repeat sequence. Therefore, a long terminal repeat was inserted into the clone by in vitro recombination, after which the most gene was able to transform NIH/3T3 cells efficiently. The nucleotide sequence encompassing the transforming region of this clone was determined. A single long open reading frame was observed, which potentially encodes a polypeptide of 41,000 daltons. This open reading frame initiates with the first five amino acids of the murine leukemia virus env gene, after which it enters the mos sequence, where it terminates. The nucleotide sequence described in this paper was compared with other sequences of mos in an effort to resolve discrepancies in the position of the long open reading frame. Although Moloney murine sarcoma virus retains the 3' splicing site of the murine leukemia virus env gene, a mos-specific mRNA which corresponds structurally to the murine leukemia virus env mRNA was not identified. The sequence described here revealed a single nucleotide change in the proposed env gene 3' splicing site which was retained in Moloney murine sarcoma virus. This deviation from the consensus 3' splicing sequence may underlie the observed absence of mos expression via the env gene splicing pathway.